Entrepreneurial Village Based on Bioindustry Automatic Distillation Essential Oil to Optimize Jasmine Flower Products (Jasminum Sp.) in Jingah Habang Ilir Village - Firdaus, Muhammad; Rahmasari, Fenny; Rahmah, Ghina Maulida; Mahindra, Haidil; Jannah, Noor; Hafidhah, Nor Jinan; Fadinah, Siti Rosyidah; Shabrina, Ahda; Fikriadi, Ahmad Bagas; Ibrahim, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2023)
Banjar Regency is the largest flower production center in South Kalimantan. As one of the flower-producing areas, Jingah Habang Ilir Village has potential in flower processing. Based on this, to develop the Jasmine Flower (Jasminum sp.) industry in Jingah Habang Ilir Village and improve the quality of the Jasmine Flower essential oil product as a superior product so that it can make a village that has a distinctive attraction in the form of products from processed Jasmine Flowers, essential oil processing from jasmine flowers is carried out as one of the economic supports in Jingah Habang Ilir Village. The approach methods used are observation, socialization, and training. This approach provides understanding through field observations, involves active participation from various parties during socialization activities, and improves practical skills through training with direct examples in essential oil processing.